Analisis Node dengan Metode Degree Centrality dan Sentiment Analysis dalam Acara G20 Indonesia di Twitter - Harnanda, Elifas Gavra; Mailoa, Evangs (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
Twitter is a popular social media platform that is used to communicate through exchanging messages and one of them can use hashtag #G20Indonesia. #G20Indonesia is a hashtag originating from the G20 Indonesia event which was held in Bali from 15 to 16 November 2022. It aims to analyze data on research containing G20Indonesia